2020
DOI: 10.3390/ma13225196
|View full text |Cite
|
Sign up to set email alerts
|

Recent Purification Technologies and Human Health Risk Assessment of Microplastics

Abstract: Microplastic (MP)-based contaminants in the environment are pervasive, but standard technologies used for MP identification have not yet been reported. Human beings take up MPs from the environmental ecosystem through the food chain without any particular purification. MPs can penetrate into capillaries from the bloodstream, resulting in endocrine system disorders or toxicity. In this review, we introduced several technologies, such as filtration using membranes, biological degradation, electrocoagulation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 100 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…Recently, MP were evaluated in various cells and animals, and determined as one of the risk factors for human health. However, conflicting results were reported for the toxicity of MP against human cells [ 4 ]. Most previous studies showed that MP induce some degree of toxicity or pathological changes in human cells, whereas few studies suggest no significant cellular toxicity, except at high concentrations [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MP were evaluated in various cells and animals, and determined as one of the risk factors for human health. However, conflicting results were reported for the toxicity of MP against human cells [ 4 ]. Most previous studies showed that MP induce some degree of toxicity or pathological changes in human cells, whereas few studies suggest no significant cellular toxicity, except at high concentrations [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within the chemical method, we also have the technique of pyrolysis-gas chromatography/ pyrolysis-mass spectrometry (Pyr-GC-MS), which combines two methodologies with pyrolysis [65]. Another technique to consider for the identifcation of MPs is scanning electron microscopy (SEM) which provides high-resolution images using the area to be studied to reveal morphological details; this study is usually complemented by energy-dispersive Xray spectroscopy (EDS) which uses a high-energy electron beam to confrm the chemical composition of the particles, as each chemical element emits X-rays with specifc energies [66]. Apart from traditional methods, various novel techniques have been developed for the detection of MPs.…”
Section: Microplastic Identifcation Approachesmentioning
confidence: 99%
“…Tese techniques can be divided into physical, chemical, and biological methods, with each method having its own advantages and disadvantages based on the source of the particles to be removed. In this section, we will discuss the latest solutions in detail, including physical methods that use magnetic principles for water purifcation, such as the magnetic nanoparticle method [66].…”
Section: Emerging Techniques For the Removal Of Microplasticsmentioning
confidence: 99%
“…Most existing toxicity assessments have investigated the physical effects of microplastic particles. Physical and chemical effects of microplastics are not analyzed separately, and the results obtained from studies represent their overall toxicities . Therefore, dose–response assessments are unable to identify the driver(s) of toxicity: the physical effect of microplastics themselves or the chemicals associated with them.…”
Section: Introductionmentioning
confidence: 99%